2001
DOI: 10.1002/dvdy.1211
|View full text |Cite
|
Sign up to set email alerts
|

Early mesodermal phenotypes in splotch suggest a role for Pax3 in the formation of epithelial somites

Abstract: The paired box containing transcription factor Pax3 is a crucial regulator of dermomyotome and muscle development. However, the allelic series of Pax3/Splotch mutants also displays characteristic vertebral column malformations, which do not result from defective dorsoventral somite pattern. Rather, vertebral column and sclerotomal phenotypes are reminiscent of the phenotypes observed in the segmentation/somitogenesis mutants rachiterata and pudgy. Moreover, rostrocaudal somite pattern and somitic boundaries ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 54 publications
4
53
1
Order By: Relevance
“…This is in contrast to studies where lethality of Pax3 Ϫ/Ϫ embryos was observed between E13.5 and E14.5 when the mutant allele was kept on an inbred background, such as a mix of C3H/101 and BA/Ca or C57Bl6 (17,18). Tbx18 Ϫ/Ϫ embryos died shortly after birth as reported before (12).…”
Section: T-box and Paired Box Interaction Is Promiscuous-we Next Invecontrasting
confidence: 66%
See 1 more Smart Citation
“…This is in contrast to studies where lethality of Pax3 Ϫ/Ϫ embryos was observed between E13.5 and E14.5 when the mutant allele was kept on an inbred background, such as a mix of C3H/101 and BA/Ca or C57Bl6 (17,18). Tbx18 Ϫ/Ϫ embryos died shortly after birth as reported before (12).…”
Section: T-box and Paired Box Interaction Is Promiscuous-we Next Invecontrasting
confidence: 66%
“…4F, arrow). However, skeletal defects were generally less severe than the ones described for Pax3 alleles maintained on inbred genetic backgrounds (17,18). Notably, and in contrast to Tbx18 mutants, the proximal ribs were unaffected, and the pedicles were spaced regularly (Fig.…”
Section: T-box and Paired Box Interaction Is Promiscuous-we Next Invementioning
confidence: 84%
“…We also focused on Pax3 or Pax3/FKHR target genes known or likely to be genetically downstream of Pax3. For example, Pax3 is required for proper epithelialization of the developing somite (Schubert et al, 2001). EPHA4, which is normally expressed in the anterior portion of newly formed somites, is misexpressed in Pax3-deficient embryos (Schubert et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…p.c.) in the myotome [33,34]. Pax3 is also present in the brain, dorsally throughout the neural tube and in neural crest cells.…”
Section: Discussionmentioning
confidence: 99%